2021
DOI: 10.1128/mra.00506-21
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Seven Cronobacter sakazakii Strains Carrying the mcr 9.1 Gene Isolated in Chile

Abstract: Cronobacter sakazakii is a pathogen that causes severe diseases such as meningitis and necrotizing enterocolitis in infants under 12 months, associated with the consumption of contaminated rehydrated powdered infant formula (PIF). We present seven C. sakazakii genome sequences isolated from PIF and dairy products in Chile in 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Additionally, we detected the presence of the mrc 9.1 gene, which confers resistance to colistin (polymyxin), considered a gene of significant concern in public health. This gene has been reported in clinical cases associated with Cronobacter sakazakii ST1, as well as isolates from foods like powdered infant formula (PIF) [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we detected the presence of the mrc 9.1 gene, which confers resistance to colistin (polymyxin), considered a gene of significant concern in public health. This gene has been reported in clinical cases associated with Cronobacter sakazakii ST1, as well as isolates from foods like powdered infant formula (PIF) [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial abuse in agricultural and clinical settings favored the development of resistance to different antibiotics in Cronobacter and then led to the spread of antimicrobial-resistant bacteria/genes in the environment ( 29 32 ). Although Cronobacter isolates are generally susceptible to the antimicrobial agents most often used clinically, resistance to one or more antimicrobials such as cephalothin and streptomycin ( 33 , 34 ) and even β-lactams or colistin ( 19 21 ) has been frequently reported recently. Our previous study showed that the resistance rate of 417 Cronobacter isolates collected from 2012 to 2014 was 1.9% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial therapy is a common treatment of clinical infection caused by Cronobacter ( 15 18 ), but the occurrence of AMR genes, especially mediated by mobile genetic elements, in this bacterium limits the therapeutic options for clinicians ( 14 ). In particular, it is worth noting that MDR and even mcr-1 - and mcr-9 -carrying Cronobacter isolates have been detected in food, clinical, and animal specimens and in samples from a dead infant fed Cronobacter -contaminated PIF ( 19 22 ). Therefore, the emergence of antimicrobial resistance, particularly MDR, in Cronobacter in infant foods has become a potential public health concern.…”
Section: Introductionmentioning
confidence: 99%